Field-Based Daily Journal: Studying Coastal Abrasion in Environmental Engineering (Collaborate Engineering Daily Book Series, 2025)
Coastal abrasion is an increasingly critical environmental issue affecting coastal ecosystems, infrastructure, and human settlements due to the combined impacts of climate change, sea-level rise, wave dynamics, and anthropogenic activities. This study presents a four-week field-based daily journal documenting coastal erosion processes in a vulnerable shoreline area through systematic observation of shoreline retreat, wave behavior, sediment characteristics, vegetation cover, and human activities. A mixed-method approach was employed, integrating quantitative measurements such as shoreline position, sediment grain size, and wave intensity with qualitative assessments including community behavior and coastal management practices. The results indicate that abrasion rates were highest in areas lacking natural vegetation buffers and in locations exposed to high-energy waves, while mangrove-covered zones exhibited significantly lower erosion. Human activities such as sand mining and coastal construction were identified as major contributing factors to shoreline instability. The study concludes that effective coastal management requires an integrated approach combining environmental engineering interventions, nature-based solutions, continuous monitoring, and community engagement to enhance coastal resilience and sustainability.
Keywords: Coastal Abrasion; Shoreline Erosion; Environmental Engineering; Mangroves; Sustainable Coastal Management